2006
DOI: 10.1063/1.2198210
|View full text |Cite
|
Sign up to set email alerts
|

The poloidal distribution of type-III edge localized modes in the Mega-Ampère spherical tokamak (MAST)

Abstract: This article describes the poloidal plasma particle distribution of type-III edge localized modes (ELMs) in the Mega-Ampère spherical tokamak [R.-J. Akers et al., Phys. Plasmas 9, 3919 (2002)]. A fast imaging camera with 10μs exposure time is used to record the Dα light coming from the entire poloidal cross section. Furthermore, three sets of probes, triggered at the same time, acquired at 1MHz, and located at different poloidal, radial, and toroidal locations in the tokamak are used. ELMs are observed to affe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
1
2
0
Order By: Relevance
“…Although the basic mechanism for the instability of the edge layer has not been fully understood up to now, it is probable that the radial electric field behind the plate is inducing the turbulence. This situation is very similar to the turbulent regimes recorded in the scrape-off-layer (SOL) of magnetically confined thermonuclear plasmas [16][17][18].…”
Section: -P1supporting
confidence: 74%
“…Although the basic mechanism for the instability of the edge layer has not been fully understood up to now, it is probable that the radial electric field behind the plate is inducing the turbulence. This situation is very similar to the turbulent regimes recorded in the scrape-off-layer (SOL) of magnetically confined thermonuclear plasmas [16][17][18].…”
Section: -P1supporting
confidence: 74%
“…A significant number of experimental investigations were dedicated to characterizing ELMs properties and the underlying radial particle and energy transport [4][5][6][7]. Visible and infrared imaging has been used to study ELMs [7][8][9][10] where filamentary structures were observed and their properties were studied in detail.…”
mentioning
confidence: 99%
“…The reason being the SOL is the region where the plasma is in direct contact with the first wall. Plasma in the SOL is mainly caused by turbulence radial transport in L-mode discharges and during ELMs in H-mode discharges [1,2]. We have dedicated several studies to unviel the different facets of turbulence properties in the SOL.…”
mentioning
confidence: 99%